Ameliorative Effects of Trichosanthes dioica Extract in Suppressing Inflammatory Mediators and Attenuating Oxidative Stress - Kharbanda, Chetna; Alam, Mohammad Sarwar; Hamid, Hinna; Javed, Kalim; Bano, Sameena; Ali, Yakub; Nazreen, Syed; Haider, Saqlain (Planta Medica, 2015)
The present study aimed to investigate the anti-inflammatory activity of the ethanolic extract of the aerial parts of Trichosanthes dioica and its successive fractions. The effect on oxidative stress involved in the pathogenesis of inflammation was evaluated. The ethanolic extract and its successive fractions were administered at a dose of 150 and 300 mg/kg b. w. for testing their anti-inflammatory activity by a carrageenan-induced edema model. The results showed that the ethyl acetate fraction exhibited significant potency against inflammation. Pertaining to mechanistic insight, the anti-inflammatory effect might be attributed to the attenuation in tumor necrosis factor-α level (ELISA assay) and reduced expression of cyclooxygenase-2 and nuclear transcription factor-κB (immunohistochemistry). The alleviation in oxidative stress has been pertinent to the elevation in the activities of antioxidant enzymes (superoxide dismutase, catalase, and glutathione) by active fractions. Furthermore, the ulcerogenic effect was insignificant even at a three times higher dose. Finally, it was concluded that the ethyl acetate fraction which showed significant biological potential against inflammation and oxidative stress could be viewed as a source of effective treatment.
Keywords: Trichosanthes dioica; Cucurbitaceae; anti-inflammatory; antioxidant enzymes